Rheumatoid Arthritis: Disorders Of Hemostasis Components - Musaeva N. B (Genius Journals, 2024)
The review contains information about the physiology of the hemostasis system and its components, and discusses the relationship between the hemostasis system and inflammation. The physiology of normal hemostasis, the interaction of platelets with endothelial cells and leukocytes, as well as with von Willebrand factor and the complement system, and their role in rheumatoid arthritis are described. Thus, platelets can be considered not only as hemostatic, but also as inflammatory cells.
Keywords: blood coagulation system; rheumatoid arthritis; inflammation